Forensic psychiatry services in Nunavut. Issue 1 (1st January 2021) - Upfold, Casey; Chaimowitz, Gary
ABSTRACT: There is a paucity of research on forensic psychiatry patients from Nunavut, including no published data concerning the prevalence and characterisation of patients in this territory. The lack of basic information hinders the evaluation of services and establishing best practices. The current paper aims to characterise forensic psychiatry patients from Nunavut and further the understanding of the challenges in organising forensic psychiatry healthcare in Nunavut. A retrospective chart review design was used to examine individuals from Nunavut who are engaged with the Ontario forensic psychiatry system. The sample included all Unfit to Stand Trial (26.7%) and Not Criminally Responsible (73.3%) patients ( N = 15) under the jurisdiction of the Nunavut Review Board in a one-year period. The average distance between the patient's place of residence in Nunavut and the Ontario facilities was 2, 517 km. Overall, 26.7% were living in Nunavut, 60.0% remained in Ontario, and 13.3% resided in Alberta. Results are presented for sociodemographics, forensic status, personal and familial history, psychiatric and criminal history, diagnoses, index offence characteristics, treatment, assessment tools, and aggression. The prevalence and many characteristics of forensic psychiatry patients from Nunavut differ from the rest of Canada and have important implications for the delivery of services.